Sosialisasi pola hidup sehat di lingkungan nelayan di Desa Teluk Latak Kabupaten Bengkalis - Rasoel Hamidy; Suyanto Suyanto; Rahmadi Rahmadi (CANANG: Jurnal Pengabdian Masyarakat, 2022)
Indonesia is known as one of the maritime countries whose territory is mostly water area. Fishermen are the largest working group in Teluk Latak Village, Bengkalis District. Fishers’ work is full of challenges and health threats due to the uncertain working terrain and working time. counseling to fishing communities is carried out by implementing health education and promotion programs in a sustainable manner, especially in practicing a healthy lifestyle. This activity was carried out on May 7, 2018, in the village of Teluk Latak, Bengkalis Regency. This activity was attended by the village head, community leaders, fishermen, and doctors of the Bengkalis Health Center. In the service activity, counseling was presented about a healthy lifestyle for fishermen, introduction to several diseases such as Dengue Hemorrhagic Fever (DHF), Tuberculosis (TB) Infection, and Diabetes. This activity received a good response from the community and it can be seen from the reaction of the community very jointly in the implementation of this service activity.